The Media Got it Wrong! A Critical Discourse Analysis of Changes to the Educational Policy Making Arena - Piazza, Peter (Education Policy Analysis Archives, 2014)
The context for education policy making has changed dramatically in recent years. Policy-making at the state-level has become characterized by near-unprecedented enactment of neo-liberal education policies, increased influence of so-called Education Reform Advocacy Organizations (ERAOs) and increased challenges to unions’ political influence. In this article, I explore the news media’s characterization of power and political influence in this new policy making arena. I offer case study analysis of a Massachusetts law, passed in the summer of 2012 with support from a non-profit advocacy group called Stand for Children, that limits seniority-based tenure for public school teachers. I use Critical Discourse Analysis to explore how themes, or discourses, common to this new context of policy making played out in the media coverage of the law, and I identify and characterize differences between media coverage of the law and the historical account as told in stakeholder interviews with major players involved in policy debate and development. Ultimately, I suggest that differences between media and interview data can tell us a lot about power and political influence in a time of dramatic policy change.